Effect of different recovery patterns on repeated-sprint ability and neuromuscular responses - Billaut, F.; Basset, F. A. (Journal of Sports Sciences, 2007)
We examined the effect of recovery pattern on mechanical and neuromuscular responses in active men during three repeated-sprint ability tests consisting of ten 6-s cycling sprints. Within each test, the recovery duration was manipulated: constant, increasing, and decreasing recovery pattern. Maximal voluntary contractions of the knee extensors were performed before and after the repeated-sprint ability tests to assess strength and electromyographic activity [root mean square (RMS)] of the quadriceps muscle. We observed different fatigue patterns for peak and mean power output between recovery patterns, with earlier decrements recorded during the increasing recovery pattern. Total work performed over the ten sprints was also lower in the increasing recovery pattern (43.8 ± 5.4 kJ; P < 0.05). However, the decreasing recovery pattern induced a greater overall power output decrement across the sprints (-15.8%; P < 0.05), compared with the increasing recovery pattern (-5.1%) but not the constant recovery pattern (-10.1%). The decreasing recovery pattern was also associated with higher post-sprint RMS values (+16.2%; P < 0.05). Therefore, the recovery pattern within successive short sprints may influence repeated-sprint ability, and may lead to greater post-sprint neuromuscular adjustments when recovery intervals decrease between sprints. We conclude that peripheral impairments caused the major differences in repeated-sprint ability between recovery patterns.